Microcirculation Inflammation Associates With Outcome in Renal Transplant Patients With De Novo Donor‐Specific Antibodies. Issue 2 (21st November 2012) - de Kort, H.; Willicombe, M.; Brookes, P.; Dominy, K. M.; Santos‐Nunez, E.; Galliford, J. W.; Chan, K.; Taube, D.; McLean, A. G.; Cook, H. T.; Roufosse, C.
<x xml:space="preserve">Abstract</x> In renal transplant patients with de novo donor‐specific antibodies (dnDSA) we studied the value of microcirculation inflammation (MI; defined by the addition of glomerulitis (g) and peritubular capillaritis (ptc) scores) to assess long‐term graft survival in a retrospective cohort study. Out of all transplant patients with standard immunological risk (n = 638), 79 (12.4%) developed dnDSA and 58/79 (73%) had an indication biopsy at or after dnDSA development. Based on the MI score on that indication biopsy patients were categorized, MI0 (n = 26), MI1 + 2 (n = 21) and MI ≥ 3 (n = 11). The MI groups did not differ significantly pretransplantation, whereas posttransplantation higher MI scores developed more anti‐HLA class I + II DSA (p = 0.011), showed more TCMR (p < 0.001) and showed a trend to C4d‐positive staining (p = 0.059). Four‐year graft survival estimates from time of indication biopsy were MI0 96.1%, MI1 + 2 76.1% and MI ≥ 3 17.1%; resulting in a 24‐fold increased risk of graft failure in the MI ≥ 3 compared to the MI0 group (p = 0.003; 95% CI [3.0–196.0]). When adjusted for C4d, MI ≥ 3 still had a 21‐fold increased risk of graft failure (p = 0.005; 95% CI [2.5–180.0]), while C4d positivity on indication biopsy lost significance. In renal transplant patients with de novo DSA, microcirculation inflammation, defined by g + ptc, associates with graft survival.